Respiratory and other organ manifestations in NKX2-1-related disorders: a systematic review - Katarzyna Michel; Katarzyna Michel; Alba Ruiz-Ramos; Laia Nou-Fontanet; Carmen Martín-Gomez; Carmen Martín-Gomez; Beatriz Carmona Hidalgo; Rebeca Isabel-Gomez; María Piedad Rosario-Lozano; Rocio Rodriguez-Lopez; Thomas O. F. Wagner; Thomas O. F. Wagner; et al. (Frontiers in Medicine)
BackgroundNKX2-1-related disorders (NKX2-1-RD) encompass a spectrum of conditions arising from pathogenic deletions or variants in the NKX2-1 gene, crucial for thyroid, lung, and brain development. Respiratory manifestations in NKX2-1-RD range from neonatal respiratory distress to severe lung diseases, constituting a leading cause of mortality. This study will review and synthesize NKX2-1-RD respiratory phenotypes, genetic alterations, and long-term trajectories.MethodsWe conducted a systematic review using PRISMA and PICO question formats. From January 2002 to July 2023, major biomedical databases and rare disease resources were searched. Genetically confirmed NKX2-1-RD patients with respiratory symptoms were eligible for this study.ResultsOut of 4,569 studies, 38 met inclusion criteria, predominantly case reports and series. The study included 148 patients, revealing diverse respiratory phenotypes and treatments. Respiratory manifestations emerged at various ages, with neonatal respiratory distress, asthma, interstitial lung disease, and lung cancer observed. Nonsense mutations in NKX2-1 were linked to lung cancer. Treatment varied, including oxygen supplementation, ventilation, antibiotics, and lung transplantation. Long-term follow-up disclosed heterogeneous respiratory outcomes, with some patients asymptomatic while others faced chronic insufficiency or recurrent infections. The overall survival of informed cases was about 60%.ConclusionThis study highlights the complex respiratory manifestations of NKX2-1-RD and their impact on patient outcomes. The findings support standardized respiratory follow-up protocols and provide clinical management insights despite study quality and sample size limitations. We discuss the challenges of treating diverse respiratory conditions in this rare clinical entity and lay the groundwork for future research.